LAND USE AS A HEALTH EDUCATION EFFORT FOR ELEMENTARY SCHOOL STUDENTS - Haifaturrahmah, Haifaturrahmah; Nizaar, Muhammad; Afandi, Ahmad; Mandala, Halus; Darmurtika, Linda Ayu; Khosiah, Khosiah (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Tujuan kegiatan pengabdian untuk memanfaatkan dengan optimal lahan yang ada disekolah khususnya di SDN 2 Jembatan Kembar, Lombok Barat. Seperti yang kita ketahui bahwa sekolah merupakan salah satu lembaga formal untuk para siswa melakukan proses pembelajaran dibawah pengawasan guru. Proses belajar tidak hanya dilakukan oleh siswa didalam kelas, namun siswa juga dapat belajar ditaman sekolah (outdoor). Sekolah harus dapat memanfaatkan dengan optimal lahan yang ada sebagai sumber belajar siswa, khususnya berkaitan dengan tanaman. lahan yang ada dapat ditanami dengan berbagai jenis tanaman yang berfungsi sebagai sayur maupun obat, dan hal ini merupakan salah satu proses pembelajaran sebagai edukasi kesehatan bagi siswa sekolah dasar.Abstract: The purpose of the devotional activities is to make optimal use of the land in schools, especially at SDN 2 Jembatan Kembar, West Lombok. As we know that the school is one of the formal institutions for students to conduct the learning process under the supervision of teachers. The learning process is not only done by students in the classroom, but students can also learn in the school park (outdoor). Schools should be able to make optimal use of existing land as a source of learning for students, especially about plants. Existing land can be planted with various types of plants that serve as vegetables and medicines, and this is one of the learning processes as health education for elementary school students.